Analisis Kelayakan Usaha Tenun Ulos yang Ada di Balige Provinsi Sumatera Utara - Sebayang, Andreas Raja Tengah; Simamora, Natalya K E; Sinuhaji, Sri Marsela Br; Sianipar, Yohana Meilina (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
This research is aimed at analyzing the feasibility of the Ulos Weaving business in Balige. This research is descriptive qualitative. Data was obtained through field studies. The results show that the analysis of legal aspects shows that this business requires supervision of the completeness of documents and the validity of documents related to legality. (b). Analysis of market and marketing aspects shows that this ulos woven product is a production product that has its advantages that are needed by the community, especially the Toba community, and has high aesthetic value and a selling price that is not too high (c). Analysis of management and organizational aspects shows that this business has carried out organizational planning and management as well as human resources, but it is still not effective and optimal. (d). Analysis of financial aspects shows that this business still carries out financial recording and reporting as small and medium businesses do in general. For this reason, more precise reporting is needed, especially under business feasibility studies so that it can be taken into consideration in decision-making both by the business owner and also by other parties.